Menyiasati Islamofobia di Barat - Dedi, Bonifasius; Murdiono, Krisantus; Theo, Kristianus; Taruki, Taruki; Franszedha, Thomas Ilyo (Perspektif, 2021)
The focus of this research study is Islamophobia in the West. The writers argue that harmony among religious communities is the noble ideal of many people. In trying to make it happens, there are always challenges trying to hinder it. Islamophobia is one such challenge. The methodology used in this study is qualitative and field studies. We use literature and interview methods to obtain information related to the theme of Islamophobia in the West. This study found that religion is a peacemaker. Beyond that is not what flows from religion. All forms of violence and discriminatory actions are not existential causes of religion. Religion never teaches violence. The study concludes that Islamophobia is a form of deviation that must be eliminated.